The impact of academic procrastination and academic performance on academic achievement amongst undergraduate students at a local university - Lily Sandhora, Kasim (2015)
This study aimed to examine academic procrastination and its relationship with academic performance among 90 students of 5th semester for the Landscape & Architecture course of the Faculty of Design and Architecture of one of the local universities. Gender was considered in this research. After analyzing the data, it was found that participants in the study exhibited moderate procrastination tendency. This study also found that academic procrastination was significantly negatively correlated with academic performance. Gender variable had no impact on academic procrastination tendency, but had some impact on the relationship between academic performance and academic achievement. At the end of the paper, limitations and implications of the paper were discussed